PERAN MEDIASI PROFITABILITAS PADA PENGARUH RASIO KECUKUPAN MODAL DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN SAHAM - Andi Kartika; Ida Nurhayati; Whidian Hardiyanti (Distribusi - Journal of Management and Business, 2022)
The aims of this study is to analyze and empirically test the impact of capital adequacy (CAR) and Loan to Deposit Ratio on profitability in IDX banking companies, analyze and empirically test the impact of capital adequacy (CAR) and the effect of Loan to Deposit Ratio on stock return in IDX banking companies, and analyze and empirically test the impact of profitability on stock return in IDX banking companies with observation period from 2015-2019 in 43 companies. The number of samples gathered by 42 companies utilizing the purposive sampling technique. The method employed in this study is path analysis, which was preceded by data normality tests and classical assumption tests. The results showed that capital adequacy proved to have a positive effect on stock returns, the Loan to Deposit Ratio had a negative effect on stock returns, and profitability was shown to have a positive impact on stock returns, giving the sense that the higher the company's profitability, it reflects the bank's ability to generate profits high by utilizing the total assets it owns, so that it will increase the rate of return on company’s stock (stock return).